Community Empowerment in Plempoh Cultural Tourism Village - Hidayat, Angger; Rahmanita, Myrza; Hermantoro, Henky (Institut Pariwisata Trisakti, 2017)
Plempoh Cultural Tourism Village possesses a unique attraction such as natural resources and cultural heritage. Collaborating with the government, entrepreneurs, academicians and media, a group of tourism awareness called Pokdarwis Prabu Boko appears to be the central group behind every development of the Plempoh Cultural Tourism Village. However, previous research reveals that poverty still appears in this village, there is lack of community confidence and knowledge related to tourism; and lack of community participation in developing the village. This research aims to study the realization and the level of community empowerment in terms of economical, psychological, social and political aspect. This research used qualitative paradigm with descriptive method and purposive sampling technique. Data is collected using interview technique, observation and documentation. The data is then validated using source triangulation. The result shows that the community empowerment efforts undertaken by village stakeholders have not been optimal because some of the tourism village stakeholders still have not given strong commitment and they have not received trust from local communities. However, there are some evidence of community empowerment progress as follows: (1) the economic empowerment has now reached the fourth stage, namely support level. (2) the psychological empowerment is at the second stage, called reinforcement; (3) the social empowerment of the community is at its fifth stage, namely Maintenance, (4) the political empowerment is at the lowest level, namely possibility.